2006
DOI: 10.1038/sj.ki.5001707
|View full text |Cite
|
Sign up to set email alerts
|

Oxalobacter formigenes: a potential tool for the treatment of primary hyperoxaluria type 1

Abstract: Primary hyperoxaluria is characterized by severe urolithiasis, nephrocalcinosis, and early renal failure. As treatment options are scarce, we aimed for a new therapeutic tool using colonic degradation of endogenous oxalate by Oxalobactor formigenes. Oxalobacter was orally administered for 4 weeks as frozen paste (IxOC-2) or as enteric-coated capsules (IxOC-3). Nine patients (five with normal renal function, one after liver-kidney transplantation, and three with renal failure) completed the IxOC-2 study. Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(139 citation statements)
references
References 31 publications
4
132
1
2
Order By: Relevance
“…Recent studies suggest a link between USD and the intestinal microbiota. For example, intestinal colonization with Oxalobacter formigenes, which degrades oxalate, is associated with lower urine oxalate levels and fewer recurrent stones (31,32), although a protective effect of exogenous Oxalobacter remains unproven (32). Advances in DNA-based sequencing may identify other bacterial communities, which will further clarify the association between stone formation and urinary or intestinal dysbiosis (Table 1).…”
Section: Microbiotamentioning
confidence: 99%
“…Recent studies suggest a link between USD and the intestinal microbiota. For example, intestinal colonization with Oxalobacter formigenes, which degrades oxalate, is associated with lower urine oxalate levels and fewer recurrent stones (31,32), although a protective effect of exogenous Oxalobacter remains unproven (32). Advances in DNA-based sequencing may identify other bacterial communities, which will further clarify the association between stone formation and urinary or intestinal dysbiosis (Table 1).…”
Section: Microbiotamentioning
confidence: 99%
“…Studies in a mouse model of type 1 PH support the possible effect of this strategy (35). Indeed, in a small unblinded pilot study of four PH patients, urine oxalate excretion fell up to 50% during 4 weeks on an oral preparation of O. formigenes (36). In this pilot study, three out of five patients with preserved renal function demonstrated a 22-48% reduction of urinary oxalate excretion while taking the first oral formulation of O. formigenes.…”
Section: Oxalobacter and Oxalate Metabolismmentioning
confidence: 84%
“…This has been well documented in both human and animal experiments [36,37] . Loss of this bacterium occurs after the use of antibiotics [38] and its restoration may have a role in treatment of hyperoxaluria.…”
Section: Role Of Oxalobacter Formigenesmentioning
confidence: 86%